Salinity evolution in the Tagus estuary relative to climate change - Rodrigues, M. (2017)
Climate change represents a potential threat for estuaries, via potential landward intrusion of saltwater, inundation of low-lying areas, acceleration in the nutrients cycling and disruption of aquatic ecosystems. The Tagus estuary, one of the largest estuaries in Europe, holds a major natural reserve and supports diverse activities, some of which may be negatively affected by the landward intrusion of saltwater (e.g. agriculture). In this study, a new three-dimensional hydrodynamics baroclinic model is implemented and validated in the Tagus estuary. A preliminary analysis of the salinity distribution relative to different river flows and sea level rise is also performed. Results show that the model adequately represents the main patterns observed, with significant improvements from previous applications. The classification of the estuary, based on the Venice system, shows contrasting situations regarding the salinity distribution for extreme river flows, and the progression further upstream of the saltwater due to mean sea level rise.